The relationship between training and development with organizational performance among non-executive employees in Universiti Malaysia Sarawak (Unimas)/ Dayang Quraisha Abg Kiprawi - Abg Kiprawi, Dayang Quraisha (2016)
This study was carried out to find out the relationship between Training Design, On the Job and Delivery Style with Organizational Performance at Development Office in Universiti Malaysia Sarawak (UNIMAS). The major objective of this study is to study the relationship between training and development with organizational performance. This study involved 128 staffs of Development Office Department in UNIMAS as respondents of the survey. Method for primary data collection was done using questionnaires. After data collection done, it was clean and analyzed using SPSS version 22. Besides, the Pearson correlation was conducted in order to investigate the association between training design, on the job training and delivery style with organizational performance. Based on the findings, all those three variables have a strong correlation on organizational performance. Further recommendations were suggested for this study.